AUDIT QUALITY INTERCESSION:FINANCIAL RATIOSAND FIRM'S VALUE - T. Husain; Ridwan Wahyudi (STIE AUB Surakarta, 2020)
ABSTRACTThis research was studied to re-function financial ratios with the proxies of CR, DER, and TATO as a determining factor in determining a firm's value while audit quality functioned as an intercession or intervening. Company value is measured based on the Tobins'Q ratio and Audit Quality using the Big-Four public accountant firms category. This type of research is causality with a quantitative approach. This research uses subjects in companies that conduct Initial Public Offerings (IPO) in 2019 as many as 53 observation data. Methods of data analysis using path analysis with the help of the program Stata/MP 14.00. The results of this study do not prove the overall hypothesis proposed regarding Audit Quality as an intermediary in the impact of Financial Ratios with Current Ratio (CR), Total Assets Turnover (TATO), and Debt-to-Equity Ratio (DER) proxies on the Firm's Value in enterprise conducting Initial Public Offerings (IPO) in 2019.Keywords:Financial Ratios, Audit Quality,Firm's Value,IPO.